Pengaruh Gaya Kepepimpinan Transformasional Terhadap Kinerja BMT (Studi Kasus di KSPPS BMT Tumang) - Hadziq Nastain; Agus Waluyo; Musalim Ridlo (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the effect of transformational leadership style, organizational commitment, job satisfaction on the performance of managers. This research was conducted at KSPPS BMT Tumang. The research was conducted by survey method (survey). Collecting data using a questionnaire based on a questionnaire. The number of samples was taken as many as 120 managers of KSPPS BMT TUMANG by purposive random sampling based on the job description. The test technique used in this study is the structural equation model (SEM) which aims to explain the relationship between exogenous variables (transformational leadership style) and endogenous variables (job satisfaction, organizational commitment, and manager performance). SEM analysis begins with the instrument validity and reliability test phase, assumption test (assumption of sample adequacy, assumption of normality, assumption of outliers), evaluation of criteria goodness of fit, and hypothesis testing. The results showed that transformational leadership style had an effect on job satisfaction, transformational leadership style had an effect on organizational commitment, job satisfaction had no significant effect on manager performance, the organizational commitment had an effect on manager performance, transformational leadership style had no significant effect on manager performance, transformational leadership style had an effect on not significant on performance through job satisfaction, and transformational leadership style affects the performance of managers through organizational commitment.